TAGANA thematic textbook: Cultivating junior high school students English proficiency with HOTS-PBL integration - Syafryadin Syafryadin; Safnil Safnil; Noermnzah Noermnzah; Dian Eka Chandra Wardhana; Abdul Gafur Marzuki; Annisa Astrid; Shynta Amalia (Studies in English Language and Education, 2024)
This study explores the effectiveness of Themed English Teaching Materials, specifically integrating Higher Order Thinking Skills (HOTS) and Problem-Based Learning (PBL) within a TAGANA (short for Taruna Siaga Bencana, or Disaster Preparedness and Response Volunteer Team) theme to bolster junior high school students motivation and proficiency in English. Addressing the need for innovative educational methods in English teaching, this research fills an existing gap by developing and assessing TAGANA-themed materials that incorporate a HOTS-PBL approach. The study carefully selected 24 English teachers from Bengkulu, Indonesia, using purposive sampling to ensure diverse representation in qualifications, experience, and teaching methods. This study evaluates the materials content validity and instructional efficacy using the five-stage ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results show that incorporating HOTS and PBL into thematic teaching materials greatly enhances students English proficiency and motivation, especially with themes like TAGANA. Expert validation affirmed the strong content validity of the materials, and data from both the experimental and control groups demonstrated significant improvements in learning outcomes. The integration of HOTS and PBL into thematic teaching materials provides valuable insights into global educational practises. By fostering students higher-order thinking and problem-solving skills and incorporating the theme of TAGANA, this approach offers a progressive methodology for English education. This model makes significant contributions to educational practises globally.